Essensialisme Dalam Perspektif Filsafat Pendidikan Islam - Muhammad Ichsan Thaib (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2015)
Essentialism is one of the streams in the philosophy of education. The emergence of this understanding is a reaction to an absolute and dogmatic symbolism medieval. Then, formulate a systematic and comprehensive concept of man and the universe, which meets the demands of the times. Essentialism flow is the view that education, which is based on the basic view of flexibility in all its forms can be a source of onset of view fickle, volatile and less focused and erratic and less stable. Therefore education should be above ground values that can bring stability and time-tested, durable and values that have clarity and selected. Essentialism Philosophy stream is a stream of philosophy that wants the man back to the old culture. They assume that the old culture that has many virtues to perpetrate human race. What they mean by that is the old culture that has existed since human civilization first thing first. But most of them pedomani is civilization since the Renaissance, which is growing and developing around age 11, 12, 13 and 14th AD. In the Renaissance it has grown with magnificent efforts to revive the science and art as well as ancient culture, especially in the days of ancient Greece and Rome. Philosophical view of Islamic education to the concept of essentialism there is a difference, between the concept of God, human beings and the natural environment. In view of the philosophy of Islamic education are all covered in the basic concepts of Islam, namely the Quran and Hadith, as well as the thinking of experts and prominent Islamic scholars.